1980
DOI: 10.1111/j.1471-4159.1980.tb07080.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Rapidly Transported Axonal Proteins in Sensory Neurons of the Frog and Rat

Abstract: 35S-labeled proteins carried by fast axonal transport in sciatic sensory axons of bullfrog and rat were separated electrophoretically on discontinuous polyacrylamide gradient slab gels. In contrast to the previously reported similarity in the electrophoretic profiles of rapidly transported proteins from functionally different neurons, we have found that there is very little correspondence in the profiles of these proteins in functionally similar neurons from two widely studied species. We also found very littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We have compared the most abundant proteins in frog and rat sciatic nerve and a set of less abundant neuronal proteins, namely those that are rapidly transported in frog and rat sciatic nerves. We have adjusted the times allowed for accumulation of rapidly transported proteins at ligatures on frog and rat sciatic nerves to offset the different temperatures of incubation used for the two preparations (Neale et al, 1980). Not every spot on the gels is an independent polypeptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have compared the most abundant proteins in frog and rat sciatic nerve and a set of less abundant neuronal proteins, namely those that are rapidly transported in frog and rat sciatic nerves. We have adjusted the times allowed for accumulation of rapidly transported proteins at ligatures on frog and rat sciatic nerves to offset the different temperatures of incubation used for the two preparations (Neale et al, 1980). Not every spot on the gels is an independent polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the electrophoretic profiles of rapidly transported proteins in the axons of different species are similar (Theiler et al, 1976;Barker et al, 1977;Bisby, 1977;Skene and Willard, 1981), although differences might have been masked by the lack of resolution and limitation of separation by size alone on the one-dimensional sodium dodecyl sulfate gels used in these studies. Neale et al (1980) reported very little correspondence in the profiles of such proteins from the sensory neurons of frog and rat, but they were unable to distinguish differences arising from alterations in relative abundance and those arising from speciesspecific, transported proteins.…”
mentioning
confidence: 98%